Attempting to Cultivate Mindsets for Boundary Spanning in Remote Indigenous Policy. Issue 4 (1st December 2017) - Brown, Prudence Robyn
Abstract: Collaboration is held to be an essential element of addressing complex problems. However, it is difficult to achieve, as it is often in tension with bureaucratic mindsets and traditions. Recently, Williams (2013) has suggested that all policy bureaucrats and program managers required to be involved with collaboration need to 'span boundaries' – to develop the capacity to build effective relationships, be able to engage 'deeply' with different parties, and understand and value multiple perspectives. A recent government initiative to improve Indigenous wellbeing in remote Australia had a strong emphasis on collaboration and partnership. However, policy actors involved in implementation resisted attempts to make them work differently, resulting in reversion to the status quo. Consistent with social practice literature, I contend that openness to changed ways of working is a critical element for success. Drawing on interviews with elite policy actors involved in the development and implementation of the initiative, the analysis finds that career public servants appear to be less open to collaboration than those who have worked outside. While I agree that boundary spanning capability is important for overcoming the pull of the status quo, the analysis suggests that diversifying the public sector workforce should supplement training efforts. Abstract : Government initiatives to improve remote Indigenous wellbeing have a strong emphasis on collaboration and partnership. While concurring with the contention that boundary spanning capability is important for overcoming the pull of the status quo, the paper suggests that diversifying the public sector workforce should supplement training efforts.